Bovine Immunology: Implications for Dairy Cattle - Vlasova, Anastasia N.; Saif, Linda J. (Frontiers in Immunology, 2021)
The growing world population (7.8 billion) exerts an increased pressure on the cattle industry amongst others. Intensification and expansion of milk and beef production inevitably leads to increased risk of infectious disease spread and exacerbation. This indicates that improved understanding of cattle immune function is needed to provide optimal tools to combat the existing and future pathogens and improve food security. While dairy and beef cattle production is easily the world’s most important agricultural industry, there are few current comprehensive reviews of bovine immunobiology. High-yielding dairy cattle and their calves are more vulnerable to various diseases leading to shorter life expectancy and reduced environmental fitness. In this manuscript, we seek to fill this paucity of knowledge and provide an up-to-date overview of immune function in cattle emphasizing the unresolved challenges and most urgent needs in rearing dairy calves. We will also discuss how the combination of available preventative and treatment strategies and herd management practices can maintain optimal health in dairy cows during the transition (periparturient) period and in neonatal calves.